2013
DOI: 10.1002/gps.3994
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter polymorphism is associated with increased apnea–hypopnea index in older adults

Abstract: Rationale A functional polymorphism of the serotonin transporter gene (5-HTTLPR) has previously been related to upper airway pathology, but its contribution to obstructive sleep apnea (OSA), a highly prevalent sleep disorder in older adults, remains unclear. Objectives We aimed to investigate the relationship between Apnea-Hypopnea Index (AHI) and genetic variations in the promoter region of the 5-HTTLPR in older adults. Methods and Measurements DNA samples from 94 community-dwelling older adults (57% fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Also, in older Caucasian, the L allele was associated with a higher AHI and a longer time spent during sleep at oxygen desaturation levels below 90%, as Schroder et al have demonstrated. 78 The L/S genotype is associated with moderate serotonin reuptake activity and is also more frequent in male patients, which can also explain the high prevalence of OSA in male patients, especially in those with an absent L/L genotype. There is an indirect proof that the presence of S allele is a protective factor against OSA.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in older Caucasian, the L allele was associated with a higher AHI and a longer time spent during sleep at oxygen desaturation levels below 90%, as Schroder et al have demonstrated. 78 The L/S genotype is associated with moderate serotonin reuptake activity and is also more frequent in male patients, which can also explain the high prevalence of OSA in male patients, especially in those with an absent L/L genotype. There is an indirect proof that the presence of S allele is a protective factor against OSA.…”
Section: Dovepressmentioning
confidence: 99%
“…Meanwhile, the 12/12 genotype was more frequent in male controls and the 12/10 genotype was overrepresented in male patients. 78 Contrarily, the study of Yue et al suggested that allele L of 5-HTTLPR and allele 10 of 5-HTTVNTR are susceptible factors for OSA in male patients. 15…”
Section: Dovepressmentioning
confidence: 99%
“…Participants were 67 community-dwelling older adults recruited through advertisements and local senior centers for the investigation of sleep and behavioral outcomes. 20 These participants had also previously been genotyped and also had completed the RAVLT.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, there have been few investigations into the genetics of oxygen saturation in other respiratory diseases, and these have mainly been restricted to candidate gene studies. Schroder and colleagues (25) found evidence for association of serotonin transporter polymorphism with decreased arterial oxygen saturation, and also with increasing apnea-hypopnea index in older adults. de Lima Marson and colleagues (26) searched for cystic fibrosis modifier genes by assessing genetic interactions with cystic fibrosis transmembrane conductance regulator gene mutations, but did not find a significant association with oxygen saturation itself.…”
Section: Previous Studiesmentioning
confidence: 99%